The reality of financial inclusion in Sudanese banks - El-Hussein, Omer Mahgoub (Journal of Economic, Administrative and Legal Sciences, 2025)
The purpose of this study was to investigate the validity of financial inclusion in Sudan during the economic crisis, the American sanctions, the developments in the field of communications technology, and the effect of the Islamic banking system and its products on financial inclusion; this should be matched with the rapid international efforts to promote financial inclusion, which is considered to be one of the pillars of sustainable development and economic growth and as an important factor to combat poverty.The researcher followed the descriptive-analytical method to attain the objectives of the study, which represented knowing the real situation of financial inclusion in Sudan. In addition to its indicators, as reflected by intentional data, is the Arab region, and as shown by the efforts exerted by the government and the working banks.The study revealed that financial inclusion in Sudan is very low for several reasons: Sudan needs to exert great efforts to attain economic recovery, as it is considered an important factor for financial inclusion; technological communications alone are not enough to realize financial inclusion. The study also had not shown any effect of the Islamic banking system on the promotion of financial inclusion. The study showed furthermore that poverty and American economic sanctions are among the reasons for low financial inclusion; moreover, the economic crisis and the armed conflicts aggravated the situation for financial inclusion.The study proposed several key recommendations. The primary ones are the automation of services by government agencies and the mandatory adoption of electronic payment gateways for government revenue payments. Financial authorities should highlight the direct digital deposit of wage payments into bank accounts of both government and private institutions. Additionally, there is a need to increase the proportion of funds allocated from banks' portfolios to microfinance.
Keywords: Financial Inclusion; Digital Services; Islamic Financial Inclusion